A importância do porto do Touro e do sítio arqueológico do Espigão das Ruivas (Cascais) entre a Idade do Ferro e a Idade Moderna - Borges, Marco (História: revista da Faculdade de Letras da Universidade do Porto, 2017)
We try to understand in which way the Porto do Touro was occupied and gave support to the navigation on a large diachrony that lasted from the Iron Age to the Modern Age. This location is flanked by the Espigão das Ruivas, an archaeological site where ceramic fragments from the Iron Age, the Roman Period and the Middle Ages were discovered, as well as the ruins of a stone structure, although there is no exact knowledge of its role.